Experience with Dopamine Agonists in the Treatment of Prolactinomas - Barabash, Nadiya; Tykhonova, Tetiana M. (Acta medica Lituanica, 2022)
The article is devoted to the conservative treatment of hyperprolactinemia of tumor origin. Cabergoline is considered as an effective treatment not only for microadenomas but also for large pituitary tumors which is illustrated by the clinical case of the patient P. The most important effects of cabergoline demonstrated in this clinical case are reduction in the size of the adenoma from macro to micro, reverse development of chiasmal syndrome with restoration of visual functions, achievement and maintenance of the target level of prolactin. Besides the article focused on the possible development of primary and secondary resistance to dopamine analogues. One of such difficult clinical scenario is illustrated by clinical case of patient M., who was treated with different dopamine analogues with the development of secondary dopamine resistance. Along with described in literature possible mechanisms for its development in our patient we also suggest the role of prolonged inadequate therapy with dopamine agonists, when the dose of the drug was not properly adjusted, despite not reaching the target prolactin level. The literature considers several ways of optimization of treatment in resistant patients but despite of this fact it remains one of unresolved problems in the management of patients with hyperprolactinemia.
Keywords: hyperprolactinemia; dopamine agonists; cabergoline; dopamine resistance